Analysis of predicted mean vote-based model predictive control for residential HVAC systems. (1st February 2023) - Wang, Junke; Jiang, Yilin; Tang, Choon Yik; Song, Li
Abstract: Model Predictive Control (MPC) is an advanced process control method that has attracted much attention in building heating, ventilation, and air conditioning (HVAC) systems. This paper analyzes the optimal precooling performance in residential buildings using MPC with two different comfort indices, namely, temperature and predicted mean vote (PMV). It first formulates, for each comfort index, an optimization problem that accounts for different factors, such as weather, home thermal condition, prediction horizon, time-of use (TOU) utility rate, and rated cooling capacity. The problem is then solved, resulting in an MPC strategy that determines the HVAC on/off control signal and minimizes energy cost over a receding time horizon while maintaining thermal comfort. The energy performance difference between temperature-based and PMV-based MPC strategies is subsequently investigated, especially in light of the interior wall surface temperature and under different combinations of the factors. Extensive simulation results demonstrated that the proposed MPC strategies are adaptive and their performances depend primarily on weather, home thermal condition, and prediction horizon, while the impact of TOU utility rate and rated cooling capacity is relatively small. Because the PMV-based MPC strategy can take advantage of the lower interior wall surface temperature due to precooling, it resulted in 8–45% cost savings for the scenarios investigated and an average increase of 0.042–0.113 in the absolute value of the PMV index compared to the temperature-based MPC strategy. Highlights: Temperature-based and PMV-based MPC strategies for building HVAC systems are developed. The energy performance difference between the two MPC strategies under different combinations of influencing factors is investigated. PMV-based strategy shows 8–45% cost savings and an average increase of 0.042–0.113 in the absolute value of the PMV index. The performance of the two MPC strategies is most dependent on weather, the home thermal condition, and prediction horizon.